Diabetes Technology-Continuous Subcutaneous Insulin Infusion Therapy and Continuous Glucose Monitoring in Adults: An Endocrine Society Clinical Practice Guideline - Peters, Anne L; Ahmann, Andrew J; Battelino, Tadej; Evert, Alison; Hirsch, Irl B; Murad, M Hassan; Winter, William E; Wolpert, Howard (The journal of clinical endocrinology and metabolism, 2016)
To formulate clinical practice guidelines for the use of continuous glucose monitoring and continuous subcutaneous insulin infusion in adults with diabetes. The participants include an Endocrine Society-appointed Task Force of seven experts, a methodologist, and a medical writer. The American Association for Clinical Chemistry, the American Association of Diabetes Educators, and the European Society of Endocrinology co-sponsored this guideline. The Task Force developed this evidence-based guideline using the Grading of Recommendations, Assessment, Development, and Evaluation system to describe the strength of recommendations and the quality of evidence. The Task Force commissioned one systematic review and used the best available evidence from other published systematic reviews and individual studies. One group meeting, several conference calls, and e-mail communications enabled consensus. Committees and members of the Endocrine Society, the American Association for Clinical Chemistry, the American Association of Diabetes Educators, and the European Society of Endocrinology reviewed and commented on preliminary drafts of these guidelines. Continuous subcutaneous insulin infusion and continuous glucose monitoring have an important role in the treatment of diabetes. Data from randomized controlled trials are limited on the use of medical devices, but existing studies support the use of diabetes technology for a wide variety of indications. This guideline presents a review of the literature and practice recommendations for appropriate device use.